(untitled) (diségno, 2022)
On April 22nd, 2022, in the magnificent location of palazzo Gravina, the historic headquarters of the University of Naples ‘Federico II’, it was held a memorial day of Anna Sgrosso, a leading figure for the Neapolitan school of Architecture and a national reference point for the scientific-disciplinary sector of Representation of Architecture. [read more]